A comprehensive evaluation of sedimentary zeolites from Turkey as pozzolanic addition of cement- and lime-based binders. (15th February 2016) - Özen, S.; Göncüoğlu, M.C.; Liguori, B.; de Gennaro, B.; Cappelletti, P.; Gatta, G.D.; Iucolano, F.; Colella, C.
Highlights: The specific surface area affects zeolite reactivity in the initial stages. Si/Al ratio controls the pozzolanic activity at longer hydration times. Among the exchanged forms, K + -clinoptilolite has the highest lime fixation capacity. Ability of lime fixation does not always lead to a better mechanical behavior. XRD is a more sensitive technique to detect reaction products than FTIR. Abstract: The pozzolanic action played by five natural zeolite-rich materials (three clinoptilolite- and one each mordenite- and analcime-bearing rocks) coming from Turkey, has been examined, evaluating also the influence of various chemical–physical parameters, such as grain size of the zeolitic materials and nature of the cation present as extra-framework component of the structure. Pozzolan activity has been estimated by the official test of the European Standards and by thermogravimetry, finding a good accordance between the two procedures. Clinoptilolite-rich rocks gave the best results, but performance turned out to depend on the specific surface area and pre-enrichment in a potassium form. Experimental data analysis demonstrated that the pozzolanic reaction is kinetically controlled by the diffusion of reactants through a layer of dense reaction products. Experimental blended cements with the five zeolite-rich rocks were also prepared and the compressive strengths measured as a function of the curing time. The effectiveness of the pozzolanic action was monitored by XRD and FTIR analyses. An accurate microstructural study of the hardened pastes was also carried out and point analysis performed, pointing out that the zeolite-lime interaction is characterized by two stages: initially zeolite subtracts calcium from the environment by cation exchange, then it acts as a true pozzolan as soon as its structure breaks down.